The Influence of Perceived Service Quality, Price Fairness, Consumer Satisfaction on Consumer Loyalty Towards Starbucks’s Consumers - Nathalia, Nathalia; Diayudha, Lanang (Dinasti International Journal of Digital Business Management, 2024)
This study aims to determine the influence of perceived service quality, price fairness, and consumer satisfaction on consumer loyalty towards Starbucks’s consumers. This study uses primary data and the data used in this study were obtained. The data in this study were processed using the Structural Equation Model – Partial Least Square (SEM-PLS) version 4. This study used a sample of 105 respondents Starbucks’s consumers who were from Jakarta and bought at least one product from Starbucks once a month. The results of SEM-PLS analysis with the t-test and P value in this study show that Perceived Service Quality and Price Fairness have a positive and significant effect on Consumer Satisfaction, Perceived Service Quality and Price Fairness have a positive and significant effect on Consumer Loyalty through Consumer Satisfaction as a mediator, Price Fairness and Consumer Satisfaction have a positive and significant effect on Consumer Loyalty. Meanwhile Perceived Service Quality has no significant effect on Consumer Loyalty.